Interleukin-27-polarized HIV-resistant M2 macrophages are a novel subtype of macrophages that express distinct antiviral gene profiles in individual cells: implication for the antiviral effect via different mechanisms in the individual cell-dependent manner - Imamichi, Tomozumi; Yang, Jun; Chen, Qian; Goswami, Suranjana; Marquez, Mayra; Kariyawasam, Udeshika; Sharma, Homa Nath; Wiscovitch-Russo, Rosana; Li, Xuan; Aioi, Akihiro; Adelsberger, Joseph W.; Chang, Weizhong; et al. (Frontiers in Immunology, 2025)
IntroductionInterleukin (IL)-27 is an anti-viral cytokine. IL-27-treated monocyte-derived macrophages (27-Mac) suppressed HIV replication. Macrophages are generally divided into two subtypes, M1 and M2 macrophages. M2 macrophages can be polarized into M2a, M2b, M2c, and M2d by various stimuli. IL-6 and adenosine induce M2d macrophages. Since IL-27 is a member of the IL-6 family of cytokines, 27-Mac was considered M2d macrophages. In the current study, we compared biological function and gene expression profiles between 27-Mac and M2d subtypes.MethodsMonocytes derived from health donors were differentiated to M2 using macrophage colony-stimulating factor. Then, the resulting M2 was polarized into different subtypes using IL-27, IL-6, or BAY60-658 (an adenosine analog). HIV replication was monitored using a p24 antigen capture assay, and the production of reactive oxygen species (ROS) was determined using a Hydrogen Peroxide Assay. Phagocytosis assay was run using GFP-labeled opsonized E. coli. Cytokine production was detected by the IsoPlexis system, and the gene expression profiles were analyzed using single-cell RNA sequencing (scRNA-seq).Results and Discussion27-Mac and BAY60-658-polarized M2d (BAY-M2d) resisted HIV infection, but IL-6-polarized M2d (6-M2d) lacked the anti-viral effect. Although phagocytosis activity was comparable among the three macrophages, only 27-Mac, but neither 6-M2d nor BAY-M2d, enhanced the generation of ROS. The cytokine-producing profile of 27-Mac did not resemble that of the two subtypes. The scRNA-seq revealed that 27-Mac exhibited a different clustering pattern compared to other M2ds, and each 27-Mac expressed a distinct combination of anti-viral genes. Furthermore, 27-Mac did not express the biomarkers of M2a, M2b, and M2c. However, it significantly expressed CD38 (p<0.01) and secreted CXCL9 (p<0.001), which are biomarkers of M1.ConclusionsThese data suggest that 27-Mac may be classified as either an M1-like subtype or a novel subset of M2, which resists HIV infection mediated by a different mechanism in individual cells using different anti-viral gene products. Our results provide a new insight into the function of IL-27 and macrophages.